Mucoadhesive polymeric systems for vaginal drug delivery: a systemic review - Hernández-González, Maryel; Rodríguez-González, Claudia; Domínguez-Acosta, Miguel; Hernández-Paz, Juan; Olivas-Armendáriz, Imelda (Revista Mexicana de Ingenieria Biomedica, 2023)
Intravaginal drug administration has many advantages in comparison to other delivery routes: its local and systemic effect, lower dosages, and easiness of administration. Furthermore, makes it a reliable and comfortable way of therapy. This route can be used to prevent and treat a wide range of conditions including, sexually transmitted infections (STIs), hormonal treatment, birth control, and cancer treatment. The dosage forms may vary from ovules, tablets, rings, gels, creams, films and many more; lately adding the mucoadhesiveness to the characteristics to reduce the waste of active molecules. This review focuses on the way mucoadhesive polymeric systems have been applied in vaginal delivery. This review presents a bibliographical compilation of results from various investigations published in scientific databases: Science Direct, SciELO, and PubMed Central. Results compiled demonstrate that the intravaginal drug administration can be an alternative form of medication for women with more stable and prolonged results than traditional routes requiring lower doses and avoiding the first-pass effect.